The development of gradient coatings for linings of braking devices - Кіндрачук, Мирослав Васильович; Тісов, Олександ Вікторович; Стебелецька, Наталя Миронівна (Technology audit and production reserves, 2014)
The paper deals with the actual problem of developing highly efficient wear-resistant materials for manufacturing service linings of brake devices. It is proposed to use composite materials, produced based on the principle of a positive gradient of mechanical properties. Such composite materials are manufactured, and tribological testing of them is carried out. As the matrix, it is proposed to use a composite eutectic alloy, based on steel 12X18H9T taking into account thermophysical properties of reinforcing phases. A thermodynamic analysis of the interaction of all the alloy components at high temperatures is performed. Complex laser treatment of surface to improve the structure and tribological properties of the surface layer is justified. As a result of the studies, the optimal ratio of the matrix material and fillers - TiB2, VC, and the influence of the filler ratio on the wear resistance of the composite material are determined. Parameters of complex laser treatment of friction surface are developed and proved. It is found that dual laser treatment with reflow of surface layer forms a layer with a positive gradient of mechanical properties and high wear resistance. Such treatment allows to reduce the disadvantages of plasma coatings and preserve the benefits of non-equilibrium state of the material. Using the developed materials will allow to improve the reliability and durability of braking systems, in which metallic friction materials are used.